Factors associated with the use of the Indonesia COVID-19 mobile app: What needs to be improved for the future personal mobile health app? - Umniyatun, Yuyun; Suraya, Izza; Rachmawati, Emma; Nurmansyah, Mochamad Iqbal (Public Health of Indonesia, 2023)
Background: Personal mobile health applications, including the COVID-19 mobile app, offer various benefits for enhancing the effectiveness of health programs. Objective: This study aimed to investigate and compare the factors associated with the utilization of the Peduli Lindungi COVID-19 mobile application, employing the behavioral theory of the Health Belief Model (HBM). Methods: This cross-sectional survey study, conducted at the Department of Public Health in two universities in South Jakarta, Indonesia, involved 744 respondents. The independent variables were derived from the Health Belief Model (HBM), including components such as perceived vulnerability, severity, benefits, obstacles, and self-efficacy. The dependent variable was the use of the COVID-19 mobile application. Results: The majority of respondents, with an average age of 19.9 years, were female. Out of the total, 51.9% (386 individuals) used the PL application in the past seven days, albeit not on a daily basis, and 86.6% utilized the application to access public facilities. Non-users primarily cited a lack of necessity due to not having traveled in the last seven days. The variable of perceived usefulness was significantly associated with application use (p <0.001). Conclusion: There is a need for increased public education regarding the application's benefits. Furthermore, the safe entrance system feature of the app, utilized for accessing public spaces, could be consistently employed to monitor and prevent the transmission of infectious diseases, including COVID-19.